2022
DOI: 10.1111/cns.13800
|View full text |Cite
|
Sign up to set email alerts
|

Curzerene suppresses progression of human glioblastoma through inhibition of glutathione S‐transferase A4

Abstract: Glioma is the most common cancer of the human central nervous system, and it is also the most lethal tumor type. 1 According to data from the International Agency for Research on Cancer (IARC) regarding the global cancer burden, tumors of the central nervous system, including gliomas, caused approximately 30,000 deaths in China in 2020, making glioma the eighth most lethal tumor type in China. Glioma tumors progress rapidly and readily migrate to the surrounding brain tissue, and they are highly insensitive to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…Following our initial observation that DM148 barely inhibited the enzyme, whereas the DM151 was the most potent inhibitor of all tested monocarbonyl compounds, exhibiting a low micromolar IC 50 value of 2.4 μΜ, their cytotoxicity effect against two glioblastoma cell lines, namely U-251 MG and U-87 MG, was evaluated. Both cell lines have been previously reported to overexpress hGSTA4-4, and downregulation by curzerene resulted in growth and invasion inhibition [ 34 ]. Similarly, it was hypothesized that this extreme difference in hGSTA4-4 inhibitory potential between DM148 and DM151 could also differentiate their cytotoxic effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following our initial observation that DM148 barely inhibited the enzyme, whereas the DM151 was the most potent inhibitor of all tested monocarbonyl compounds, exhibiting a low micromolar IC 50 value of 2.4 μΜ, their cytotoxicity effect against two glioblastoma cell lines, namely U-251 MG and U-87 MG, was evaluated. Both cell lines have been previously reported to overexpress hGSTA4-4, and downregulation by curzerene resulted in growth and invasion inhibition [ 34 ]. Similarly, it was hypothesized that this extreme difference in hGSTA4-4 inhibitory potential between DM148 and DM151 could also differentiate their cytotoxic effects.…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin is the primary constituent of turmeric ( Curcuma longa ) extract, which contains numerous active compounds, among which curzerene, a sesquiterpene, has been shown to downregulate the expression of human hGSTA1-1 in lung cancer, resulting in tumor inhibition [ 33 ]. Curcumin is also among the very few reported compounds that inhibit in vitro the expression of hGSTA4-4 [ 34 ]. Interestingly, treatment of glioblastoma cells with curzerene resulted in lower expression of hGSTA4 mRNA and protein leading to a time-and dose-dependent manner inhibition of the proliferation, invasion, and migration of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…GSTA4 is a phase 2 detoxifying enzyme that modulates cell proliferation and apoptosis by regulating lipid peroxidation. Previous studies have reported that decreased expression of GSTA4 is associated with positive outcomes in glioma models ( Cheng et al, 2022 ), whereas increased expression of GSTA4 promotes the malignant progression of liver cancer ( Liu et al, 2017 ). Notably, GSTA4 is involved in SMC proliferation ( Luo et al, 2018 ) and may thus play a vital role in the pathological process of IA.…”
Section: Discussionmentioning
confidence: 99%
“…By catalyzing conjugation reactions of metabolites of lipid peroxidation to glutathione (GSH), GSTA4 participates in regulating cell proliferation and apoptosis ( Laborde, 2010 ). GSTA4 is expressed in the cerebral cortex and brainstem and is involved in the development of gliomas ( Cheng et al, 2022 ). Overexpression of human GSTA4 in carotid arteries can reduce neointimal formation after carotid allografts ( Xu et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that MMP is localized in vasculature cells and tumour cells of malignant astrocytomas 145 . MMP inhibition significantly decreases invasion, migration and tumour progression in advanced glioma cells 146 . All of the tumour cells would upregulate glycolysis to reduce the energy supplied by mitochondrial.…”
Section: Tumour Microenvironment Is the Main Medium For The Prolifera...mentioning
confidence: 99%